HUBUNGAN ANTARA PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) OLEH MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR (PGSD) DENGAN KEMAMPUAN SELF-EFFICACY - Dwi Magfirah, Anugrah; Al Mukarramah, Salwa; Risdayanti; Aulia, Siti; Hanika, Zahnas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the correlation between Artificial Intelligence (AI) utilization among Elementary School Teacher Education (PGSD) students and their level of academic self-efficacy. A quantitative approach was employed using simple Pearson correlation analysis. The research involved 20 students as participants. Data collection was carried out through an online questionnaire based on a Likert scale ranging from 1 to 5, comprising 10 statement items, with the first 5 items measuring AI usage (X) and the remaining 5 items assessing self-efficacy (Y). Statistical analysis revealed a Pearson correlation coefficient of r = 0.859 with p < 0.001, confirming a highly significant and strong positive association between the intensity of AI use and the academic self-efficacy of PGSD students.